Product-Service Systems – From Customer Needs to Requirements in Early Development Phases - Ericson, A.; Müller, P.; Larsson, T. C.; Stark, R. (Cranfield University Press, 2009)
Framed by Product-Service Systems (PSS), this paper discuss how needs and requirements are applied in early phases. In product development literature these and closely related terms are mixed, and a focus on gathering customer information about goods and their use guides the development team. This theoretical study highlights that lifecycle commitments such as PSS insist on the generation of a broader information basis. The application of a divergent view on goods, their use and the customers is likely to provide such information basis. The discussion provides a proposal of a simple model to set needs and requirements in relation.
Organised by: Cranfield University
Keywords: Product-Service Systems; Needs; Requirements; Engineering Design; Early Development Phases